Analysis of Work Climate and Workload to Work Loyalty PT. Dodorindo Jaya Abadi Tanjung Morawa - Siska Siska; Robin Robin (Institute of Computer Science (IOCS), 2022)
This study aims to determine the effect of work climate and workload on work loyalty at PT. Dodorindo Jaya Abadi Tanjung Morawa. This type of research is explanatory research. The population in this study were all employees of PT. Dodorindo Jaya Abadi totals 447 employees. The sampling technique used the Slovin sample where 82 samples were obtained. In this study, the questionnaire will be distributed as measured by a Likert scale. Data analysis used multiple linear regression analysis and coefficient of determination as well as simultaneous and partial tests. The results showed that the work climate and workload partially or simultaneously had a positive and significant effect on work loyalty at PT. Dodorindo Jaya Abadi Tanjung Morawa. Based on the results of this study, the implications for management are to further improve the work climate and reduce the workload.